Diphones In Sura Saba (Journal of Namibian Studies : History Politics Culture, 2023)
Muslims are attached to the Holy Quran, which is stable and perpetual. But what is striking, and calls for contemplation, is that some readers confuse the sounds of the language. The reason for this is either due to the closeness in terms of the place of articulations, as in the two soundsق /q/and غ/ɣ/ or the reader resorting to the ease he finds in expelling the sound from other than its place of articulation, in order to reduce the muscular effort. It may also be the result of the influence of local dialects and slangs on our tongues. The language and its sounds are in a state of persistent change and continuous development. This is the main motive behind this research "Diphones in Sura Saba".The aim of this research is to show the correct reading of the Holy Qur’an at the level of sounds' articulation and their characteristics. It also aims to attract the reader's attention to the closely-articulated sounds, in the form of phonemic pairs, until he performs the correct pronunciation.Minimal pairs in the language may take the form of a complete match between two words, in which one of the sounds differs, and this type is not abundantly available in the selected Holy Sura. The diphones mentioned in the selected Holy Sura are words that contain the two sounds being compared, and they differ in terms of the position of the sound in the word, and in terms of the neighboring sounds. By repeating these sounds in the same verse, the difference may become clear. The limits of this research were represented in Sura Saba, and it included practices on the correct pronunciation.The findings of the study showed that similar sounds require articulation practice so that the difference becomes clear and correct pronunciation is established. The story of Saba, which is mentioned in the selected Holy Sura, contains sermons for those who disbelieve in the blessings of God, and it shows God's honoring of His prophets and harnessing the natural conditions for them.